A Review of Image Denoising Using Fuzzy and Wiener Filters in the Wavelet Domain - Geetika Agotra,; Prof. Manish Kumar Singhal, (International Journal of Scientific Research in Science and Technology, 2024)
This paper focuses on image denoising using fuzzy wavelet domain transforms, reviewing recent advancements in this area. Wavelet transforms have become a powerful tool in image denoising, with one of the most widely used techniques involving thresholding wavelet coefficients. The paper proposes a hybrid denoising method that combines the wavelet transform, median filtering, and nonlinear diffusion. Additionally, a novel fuzzy filter is introduced to reduce additive noise in digital color images. Two distinct image denoising techniques are discussed: the first employs an Asymmetrical Triangular Moving Average Filter (TMAV) with a HAAR wavelet transform, while the second utilizes an Asymmetrical Triangular Median Filter (TMED) with the HAAR wavelet transform.
Keywords: ATMED; ATMEV; RMSE; PSNR; Wavelet Transform